الأزمة المالية العالمية بين اقتصاد السوق واقتصاد المشاركة التداعيات والحلول - دراسة مقارنة - - فيشوش, حمزة (Université de M'sila)
تتضمن هذه الأطروحة مدخلا تعريفيا للأزمات المالية والاقتصادية منذ عام 1929- 2008 م، مع التركيز على الأزمة المالية العالمية التي وقعت عام 2008 وخلفيتها وأسبابها وتداعياتها وكيفية الاستجابة لها والتعامل معها في ظل اقتصاد السوق. وتستعرض هذه الاطروحة السلبيات الكثيرة التي تمخضت عن النظام الرأسمالي، والتي تتجلى آثارها واضحة عن الحالة الاقتصادية والاجتماعية وظهور الأزمات المالية للدول، وهذا ما أدى إلى التفكير في بديل يقينا من الأزمات المالية، ولعل هذا البديل يمكن البحث عنه في اقتصاد المشاركة القائم على أصول ومفاهيم الشراكة التي تجمع بين الفعالية الاقتصادية والعدالة الاجتماعية. وتم في هذه الأطروحة اختيار دوافع ومبررات لدراسة هذه المظاهر السيئة، ومقترحين ما نعتقد أنه يتناسب مع الظروف الحالية لتحقيق النمو الاقتصادي للدول، آملين أن تلعب دورا أكبر للقضاء على ما أفرزه التحول الاقتصادي العالمي الراهن والمتمثل أساسا في ظهور أزمات مالية في ظل القيم السائدة في المجتمعات. This thesis includes an introduction to the financial and economic crisessince 1929-2008, focusing on the global financial crisis that took place in 2008, its background, its causes and repercussions, how to respond to them and deal with them in a market economy. This thesis explores the many negatives that have resulted from the capitalist system, which have clear implications for the economic and social situation and the emergence of financial crises of countries. This has led to the thought of a safe alternative to financial crises. This alternative may be sought in a participative economy based on the foundation and concepts of partnership which combines economic effectiveness with social justice. In this thesis, we choose motives and justifications to study these bad phenomena and suggest what we think is appropriate to the current conditions for achieving the economic growth of the countries, hoping it would to play a bigger role to eliminate the effects of the current global economic transformation, which is mainly the emergence of financial crises under the values prevailing in societies .
Keywords: اقتصاد المشاركة - الاقتصاد الاسلامي – اقتصاد السوق - النظام الرأسمالي – الأزمة المالية العالمية 2008 . ( the participative economy - Islamic economy - the market economy- the capitalist system- the global financial crisis2008 )